Leadership and Learning Agility: A Lifelong Journey for W. Warner Burke. (December 2020) - Hoff, David F.; Smith, David E.
Learning agility (LA) has become recognized as a key component to leadership success. The willingness to take action in new situations is paramount in today's VUCA (volatile, uncertain, complexity, and ambiguous) world. This is the story of Warner Burke's ongoing journey with LA and leadership. It defines LA and highlights its importance in organizations, follows the journey from idea to implementation and shows how Burke's efforts have led to an assessment tool that affects selection to leadership development and succession planning. This article also discusses the potential of the Burke LA assessment tool to add value in organization development efforts.